2009
DOI: 10.1111/j.1365-2435.2008.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

The sweet smell of success: floral scent affects pollinator attraction and seed fitness in Hesperis matronalis

Abstract: Summary 1.Patterns of floral scent are generally assumed to have been shaped by pollinator-mediated natural selection. However, while many studies document behavioural responses of pollinators to floral scent, few document the relationship between floral scent and fitness. 2. In this study, we explore the effect of variation in floral scent emission in colour polymorphic Hesperis matronalis on both pollinator visitation and seed fitness. 3. Using target inflorescences augmented with colour-specific floral scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 67 publications
1
82
0
1
Order By: Relevance
“…Empirical studies have shown that phenotypic and genetic variation in nectar traits can have signiÞcant direct and indirect impacts on pollination success (Galen and Newport 1988, Mitchell 2004, Salzmann et al 2007, Majetic et al 2009). In our study, pistillate ßowers produced signiÞcantly more nectar than staminate ßowers.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies have shown that phenotypic and genetic variation in nectar traits can have signiÞcant direct and indirect impacts on pollination success (Galen and Newport 1988, Mitchell 2004, Salzmann et al 2007, Majetic et al 2009). In our study, pistillate ßowers produced signiÞcantly more nectar than staminate ßowers.…”
Section: Discussionmentioning
confidence: 99%
“…For the preparation of flower extracts, freshly picked flower heads/corymbs were weighed and transferred into pentane (10 mL g À1 fresh weight) as described in Majetic, Raguso & Ashman (2009). The glass container was sealed with parafilm and stored for 20 min at 4°C.…”
Section: Flower Extractsmentioning
confidence: 99%
“…Recent experiments with volatile cues have highlighted the complexity of their function. Experimentally augmenting floral scent increased pollinator attraction for Hesperis matronalis [46], but only with specific components of its floral bouquet. In contrast, a similar experiment with Curcurbita pepo had no effect on pollinators but increased visits from florivores [47].…”
Section: Attracting More Of Whatever Pollinators There Arementioning
confidence: 99%